2006
DOI: 10.1515/cclm.2006.093
|View full text |Cite
|
Sign up to set email alerts
|

The reduction of cholesteryl linoleate in lipoproteins: an index of clinical severity in β-thalassemia/Hb E

Abstract: This study suggests that cholesteryl linoleate is the primary target of oxidative modification induced by NTBI in beta-thal/Hb E patients and that reduction in cholesteryl linoleate in lipoproteins could be used as a severity index for beta-thal/Hb E.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 34 publications
2
15
1
Order By: Relevance
“…These results support a possible role of oxidative stress in the decrease in paraoxonase activity in b-thalassemia/hemoglobin E patients. 29 Unlike the earlier studies, 28,29 there was no correlation among TAC, TOS, OSI, and paraoxonase, arylesterase in this study. However, there was negative correlation between LOOH and paraoxonase.…”
Section: Discussioncontrasting
confidence: 84%
“…These results support a possible role of oxidative stress in the decrease in paraoxonase activity in b-thalassemia/hemoglobin E patients. 29 Unlike the earlier studies, 28,29 there was no correlation among TAC, TOS, OSI, and paraoxonase, arylesterase in this study. However, there was negative correlation between LOOH and paraoxonase.…”
Section: Discussioncontrasting
confidence: 84%
“…The existence of NTBI has been assumed to be a potential risk for heart and other organ damage. We have previously observed a significant correlation between NTBI and lipid peroxidation of low density lipoprotein from b-thal/ Hb E patients [30]. In this study, correlation between NTBI and DMPO-C or ascorbyl radical indicated that NTBI partially contributes to the generation of free radical in serum of the thalassemic patients.…”
Section: Discussionsupporting
confidence: 53%
“…In addition, low levels of antioxidants in thalassemic serum could also be a factor for the presence of DMPO-C adduct. Negligible levels of serum a-tocopherol and other antioxidants have been previously reported in thalassemia subjects [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Levels of a-tocopherol, free cholesterol and cholesteryl esters in plasma, LDL and HDL were determined using an HPLC method described elsewhere (12). Plasma triglycerides and total cholesterol were measured using commercially available enzymatic assay kits (B.M.…”
Section: Levels Of Lipids A-tocopherol and Cholesteryl Estersmentioning
confidence: 99%
“…Oxidative stress and the degree of clinical severity have been shown to be related to abnormal lipid composition of lipoproteins in these patients (12). Oxidative stress and the degree of clinical severity have been shown to be related to abnormal lipid composition of lipoproteins in these patients (12).…”
Section: Introductionmentioning
confidence: 99%